2008
DOI: 10.1089/clo.2007.0065
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Migration, and Differentiation of Sox1–GFP Embryonic Stem Cells in Coculture with an Auditory Brainstem Slice Preparation

Abstract: The poor regeneration capability of the mammalian hearing organ has initiated different approaches to enhance its functionality after injury. To evaluate a potential neuronal repair paradigm in the inner ear and cochlear nerve we have previously used embryonic neuronal tissue and stem cells for implantation in vivo and in vitro. At present, we have used in vitro techniques to study the survival and differentiation of Sox1-green fluorescent protein (GFP) mouse embryonic stem (ES) cells as a monoculture or as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 62 publications
4
19
0
Order By: Relevance
“…At the time of fixation, OHCs were about 100 μm thick as they get thinner after a few days in culture [9395]. Immunostaining with a polyclonal rabbit antibody against GFAP (Dako, Carpinteria, CA, USA Cat# Z0334, RRID: AB_2314535) was conducted directly on the insert membrane, which was cut out around the OHCs [34, 94, 96]. Additionally, OHCs that were pretreated with either Annexin V conjugated to Alexa 488 (ThermoFisher Scientific) or 10,000 kDa Dextran (Dex10) conjugated to Alexa 488 (ThermoFisher Scientific), as described below, were gently peeled from the membrane insert and immunostained against GFAP (Dako) using the free-floating sections method [97].…”
Section: Methodsmentioning
confidence: 99%
“…At the time of fixation, OHCs were about 100 μm thick as they get thinner after a few days in culture [9395]. Immunostaining with a polyclonal rabbit antibody against GFAP (Dako, Carpinteria, CA, USA Cat# Z0334, RRID: AB_2314535) was conducted directly on the insert membrane, which was cut out around the OHCs [34, 94, 96]. Additionally, OHCs that were pretreated with either Annexin V conjugated to Alexa 488 (ThermoFisher Scientific) or 10,000 kDa Dextran (Dex10) conjugated to Alexa 488 (ThermoFisher Scientific), as described below, were gently peeled from the membrane insert and immunostained against GFAP (Dako) using the free-floating sections method [97].…”
Section: Methodsmentioning
confidence: 99%
“…The BS slices in our model maintain their three-dimensional organization for up to five weeks in culture, and, thus serve as a controlled organotypic system where various experimental approaches for AN reconstruction can be evaluated, including pharmacological treatments and a cellular SGN replacement therapy [42]. We have reported that mouse ESCs survive well and have an increased neuronal differentiation when co-cultured with the BS slice as compared to in monoculture [40], [41] …”
Section: Introductionmentioning
confidence: 92%
“…These can be not only derived from embryonic stem cells (ESCs) but also found within the adult nervous system [9]. In vitro , we have demonstrated the capability of several different cell types to integrate into the cochlear nucleus, being the second order neuron in the auditory neuronal pathway [1012]. Furthermore, in a previous in vivo study we demonstrated good survival and differentiation of mouse tau-green fluorescent protein (GFP) embryonic stem cells transplanted to the AN in deafened rats [13].…”
Section: Introductionmentioning
confidence: 99%